2022
DOI: 10.1371/journal.pone.0273985
|View full text |Cite
|
Sign up to set email alerts
|

Mycoparasitism capability and growth inhibition activity of Clonostachys rosea isolates against fungal pathogens of grapevine trunk diseases suggest potential for biocontrol

Abstract: The present study aimed to examine the capability of Clonostachys rosea isolates as a biological control agent against grapevine trunk diseases pathogens. Five C. rosea and 174 pathogenic fungal strains were isolated from grafted grapevines and subjected to in vitro confrontation tests. Efficient antagonism was observed against Eutypa lata and Phaeomoniella chlamydospora while mycoparasitism was observed to the pathogens of Botryosphaeria dothidea and Diaporthe spp. pathogens in in vitro dual culture assays. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…This behavior is according to the activation of several mechanisms, such as secreted enzymes to degrade the cell wall, antifungal secondary metabolites production, and plant defense systems induction. Besides having significant biocontrol activity, C. rosea also functions in the biodegradation of plastic waste, biotransformation of bioactive compounds, and source of bioenergy (Sun et al 2020;El-Gendi et al 2022;Geiger et al 2022;Kiruba and Saeid 2022;Kapeua-Ndacnou et al 2023). The findings in this study complement the benefits provided by C. rosea that were previously studied.…”
Section: Discussionsupporting
confidence: 74%
“…This behavior is according to the activation of several mechanisms, such as secreted enzymes to degrade the cell wall, antifungal secondary metabolites production, and plant defense systems induction. Besides having significant biocontrol activity, C. rosea also functions in the biodegradation of plastic waste, biotransformation of bioactive compounds, and source of bioenergy (Sun et al 2020;El-Gendi et al 2022;Geiger et al 2022;Kiruba and Saeid 2022;Kapeua-Ndacnou et al 2023). The findings in this study complement the benefits provided by C. rosea that were previously studied.…”
Section: Discussionsupporting
confidence: 74%
“…These two strains, UCD 8344 and UCD 8189, were inefficient in a dual-culture assay against E. lata. Five endophytic C. rosea strains obtained from grapevine were effective in inhibiting E. lata growth in vitro, without any direct contact [40]. John et al (2005) showed that the treatment of pruning wounds by spores of the saprophyte Fusarium lateritium reduced the recovery of E. lata when the antagonist was applied at least 1 day before the pathogen in a glasshouse assay, as well as on 16 year old healthy vineyards of the cultivar Cabernet Sauvignon in South Australian.…”
Section: Biocontrol Using Other Fungimentioning
confidence: 99%
“…Initial assessment of antagonistic interactions between microorganisms involves the in vitro dual culture bioassay, often using a nutrient-rich PDA medium [ 45 , 46 , 47 , 48 ]. Recently, a bioassay with a dual PDA culture enabled the selection of several Trichoderma strains capable of complete overgrowth and sporulation on the mycelium of several Fusarium species [ 36 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%